The creation of a risk-based insurance policy for the print collection of the UP Main Library based on the risks of fire damage and factors leading to rebinding and replacement - Ramirez, Jess Christian D. (2015)
The UP Main Library serves as the "heart" of the University. Consisting of three majors divisions: Technical Service, Administrative Service and User Education and Services Division, the UPML performs the task of being the primary information resource of the students, faculty, staff and the community of UP Diliman.